FAKTOR-FAKTOR YANG MELATARBELAKANGI KEPUTUSAN KONSUMEN MENGGUNAKAN JASA LAYANAN GRABFOOD PADA APLIKASI GRAB DI KOTA DENPASAR - SETIAWATI, NI KADEK; SUKARSA, I KOMANG GDE; GANDHIADI, G.K.; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 11 No 2 (2022)DO - 10.24843/MTK.2022.v11.i02.p364, 2022)
Grabfood is one type of online food delivery services. This services can be an alternative when people want to buy foods or drinks but cannot leave their activities. Knowing the consumer’s decision to use Grabfood is important because it such one of effort to improve the quality of this services. This research is aimed to determine factors behind consumer’s decision for using Grabfood services on the Grab application in Denpasar City. The method used in this research is factor analysis by analyzing the assessment of 120 respondents whom domiciled in Denpasar City and have used Grabfood services at least three times a month . Based on the results, there were five factors behind consumer’s decision for using Grabfood services in Denpasar City. Those factors are reliability factor of drivers, the ease of obtaining orders, informative and responsive factors for consumers, order assurance factors, and consumer care and understanding factors. Those five factors were able to explain the factors behind consumer’s decision for using Grabfood service on the Grab application in Denpasar City by 63.99%.